The Black Arts Movement : literary nationalism in the 1960s and 1970s - Smethurst, James Edward (John Hope Franklin series in African American history and culture., 2005)
James Smethurst examines the formation of the Black Arts Movement and demonstrates how it influenced the production and reception of literature and art in the US. The Movement, he argues, changed American attitudes to the relationship between popular culture and "high" art and transformed public funding for the arts.